Geo-spatial approach for suitable location of transportation terminals in the coastal towns planning - Hadipour, Mehrdad; Pourebrahim, Sharareh; Mazlin Mokhtar,; Shaharudin Idrus, (Institut Alam dan Tamadun Melayu, Universiti Kebangsaan Malaysia, 2016)
Good establishment of transportation terminals (jetties and airports) of coastal towns in proportion to relevant landuses and urban networks is an important element in urban tourism planning. Increasing urban network has both positive and negative impacts. Accessibility is chosen as key elements with respect to its critical roles in quality and attraction of coastal tourism. The overall objective of this study is to develop a decision support tool to plan appropriate locations for jetties, airport and urban transportation network development through the use of spatial technologies to address the issues of accessibility. Langkawi Island, an important tourism city in Malaysia has been chosen as a case study. This method can explain the linkage between accessibility and tourism quality. It covers the optimum accessibility from Jetties and airport to tourism landuses and facilities area. This research has successfully managed to develop a scientifically based approach to convert conceptual configuration of accessible tourism locations into transportation terminals using geospatial technology. It is hoped that this spatial based approach can be employed in transportation planning and urban network suitability assessment at both the local and structure plan levels.